Adsorptive Performance of Nanoscale a-Al2O3 Towards La(III) - Zhai, Qing-Zhou; Chen, Lu-Guo (Asian Journal of Chemistry, 2011)
Nanomaterials are ideal adsorptive materials for trace element and have great potential. In this paper, the preparation of a-Al2O3 and its adsorptive and desorptive properties towards La3+ in aqueous phase were studied. The effect of pH, temperature and time on the adsorption of La3+ by nanoscale a-Al2O3was discussed. The results showed that the adsorptive effect of the a-Al2O3on La3+ is the best over the range of pH 5-7. Adsorptive rate increases with increasing temperature, but the effect of temperature is not high. Thus, the adsorption is generally carried out at room temperature. When adsorptive time is 20 min, the adsorptive ratio is the highest and reaches 92.14 %. It is found for the studies of desorptive conditions that when 0.1 mol/L AcOH was used as an adsorbent, the desorptive effect of La3+ was better. When the desorption was 6 h, the desorptive ratio reached to 97.03 %.